Proyecto socioeducativo para la prevención del maltrato infantil con padres, madres y educadoras del Centro Infantil del Buen Vivir Luz y Vida. - Pilatasig Patango, Gloria Margarita (2017)
The work of educational intervention is an effort of the career of Intercultural bilingual education to contribute to the prevention of child abuse in children's centres of good living experience focused on the province of Cotopaxi. This proposal is the narrative of the experience of the project educational partner for the prevention of child abuse with parents and educators of the child center of good living "Light life". Describes the forms or types and causes of abuse identified by the parents through the diagnostic workshops. Also proposed in document the narration of the experience developed in scenario workshops, the paper ends with conclusions and recommendations on the carried out experience.